The Nattukottai Chettiar Temple: An architectural manifestation of chettier cultural identity (ARTEKS : Jurnal Teknik Arsitektur, 2025)
The Chettiar moneylenders from Chettinad, Tamil Nadu, India, thrived in local and international commerce, especially in the Malay States. Their architecture, influenced by finances, banking, and trade, is simultaneously unique and culturally significant. The Chettiar community in Penang is facing a population decline. Thus, the community's cultural neglect leads to its demise. Despite the Chettiar community's longstanding involvement in commerce, banking, and financial management, more comprehensive research needs to be conducted to explore the influence of these factors on their architectural designs, particularly their temples. The potential demise of Chettiar culture raises significant concerns about the need for more experts in this field, highlighting the urgent need to preserve their architectural heritage. The primary aim of this qualitative method is research to study the architectural features of the Chettiar temple. It delves into the temple's architectural design, exploring the distinctive features that represent a fusion of multiple cultures. The study assesses their impact on enhancing the temple's visual appeal and cultural significance. The temple, a representation of the magnificence and intricacy of architectural craftsmanship, stands as evidence of the Chettiars' economic prosperity. Furthermore, the research examines the functional characteristics of the temple space, offering a deeper understanding of its design and usage. The study also analyses the historical development of trade associated with the Chettiar temple in the Malay states. This study seeks to explain the complex interconnections of culture, architecture, and commerce, with the ultimate goal of preserving the Chettiar community's unique cultural and architectural heritage.
Keywords: Architectural analysis; Architectural influence; Chettiar community; Cultural heritage preservation; Trade